Time-multiplexed multi-view three-dimensional display with projector array and steering screen - Xia, Xinxing (2019)
A novel time-multiplexed multi-view three-dimensional (3D) display has been implemented using a projector array to provide the image source and an angular steering-screen module to generate multiple high density horizontal views. The liquid crystal (LC)-based steering screen was specially developed to deflect light beams over a small range and operate in synchronism with the projector array with the use of a customized FPGA driver. The prototype produces vivid color 3D scenes with smooth parallax to multiple viewers. The experimental results verify the proposed multi-projection time-multiplexed multi-view 3D display method that uses a steering screen to produce dense views. Displaying both static and dynamic 3D contents is achieved in our implemented 36-view 3D display prototype. The results of crosstalk measurements are given and analyzed to evaluate the display performance.